Mitigating Delay Impacts in Construction Projects: An Evaluation of Causes and Strategies - Ijaz, Ahmad; Syed, Saad; Syed Nouman, Shah; Muhammad, Bilal; Fabiha Fatima, Agha; Sumayya, Obaid (INTI International University, 2024)
Construction plays a crucial role in driving national economic growth for sustainable development. Nonetheless, delays in many building projects emerged due to various challenges. Identifying and addressing these delays proved essential for ensuring project success. Timely completion stood as a key indicator of project success, whereas delays could result in increased costs and disputes among stakeholders. This study aimed to explore the causes of delays in construction projects and their remedial measures. Specifically, the research investigated delay factors in construction projects across Khyber Pakhtunkhwa, including the Machai Hydro Power Project in Mardan, the Golen Gol Hydro Power Project in Chitral, the KOTO Hydro Power Project in Lower Dir, and the rehabilitation of the Peshawar to Dara Adam Khel carriageway. Data was collected through Google Forms, with participants providing valuable responses. The analysis was conducted using IBM SPSS. Results indicated that land acquisition, client issues, consultant problems, general factors, and budget conflicts had the most significant impact on delays. This study offered important insights into the construction industry, highlighting strategies to mitigate these issues and improve project efficiency.